P.016 Early telephone follow-up for traumatic brain injury patients using the Rivermead post-concussion symptoms questionnaire. (2nd June 2017) - Thibault-Halman, G; Fenerty, L; Taylor, P; Kureshi, N; Walling, S; Clarke, DB
Abstract : Background: Patients who require hospitalization for a mild or moderate traumatic brain injury (TBI) are often discharged home with uncertainty around their full recovery. This study examines the frequency and severity of common post-TBI symptoms, as assessed by the Rivermead Post-Concussion Symptoms Questionnaire (RPCQ).Methods: All adult TBI inpatients discharged home from the Neurosurgery service were interviewed by phone at two weeks by a rehab-based nurse practitioner. RPCQ components (cognitive, emotional, and somatic) were analyzed; findings and management recommendations were communicated to family practitioners and the treating neurosurgeon.Results: In 46 patients, cognitive symptoms were present in 52%, 91% had somatic, and 100% had emotional symptoms. Fatigue was the most common symptom (67%). Double vision was the least common symptom (4%). Recommendations for managing symptoms, return to work, and need for formal clinical assessment were provided for 37% of cases.Conclusions: All patients admitted to neurosurgery with mild or moderate TBI had symptoms at two weeks. The RPCQ is a low-cost structured evaluative tool which highlights needs and provides guidance for patients and care-givers; it also seems effective in identifying those who may require formal clinical assessment.